Group 2 metal (Mg, Ca, Sr) silylamides supported by a cyclen-derived macrocyclic polyamine. Issue 26 (19th June 2017) - Mukherjee, Debabrata; Shirase, Satoru; Beckerle, Klaus; Spaniol, Thomas P.; Mashima, Kazushi; Okuda, Jun
Abstract : [M{N(SiMe3 )2 }2 ] and [M{N(SiHMe2 )2 }2 ] (M = Mg, Ca, Sr) reacted with the macrocyclic NNNN-type polyamine (Me3 TACD)H (LH) to give different types of products, especially with the β-SiH function, exhibiting the individuality of these alkaline earths within the identical ligand sets. Abstract : Heteroleptic bis(silyl)amides of magnesium and calcium [(L)M{N(SiMe3 )2 }] [M = Mg, Ca; LH = 1, 4, 7-trimethyl-1, 4, 7, 10-tetraazacyclododecane; (Me3 TACD)H] were previously synthesized from LH and [M{N(SiMe3 )2 }2 ]. Strontium bis(silyl)amides [Sr{N(SiMe3 )2 }2 (thf)2 ] and [Sr{N(SiHMe2 )2 }2 (thf)2/3 ] reacted with LH to give different types of products, depending on the presence of the β-SiH function. While the former underwent protonolysis to give the amido-bridged dimer [(L)Sr{N(SiMe3 )2 }]2 (1 ), the latter gave the adduct [(LH)Sr{N(SiHMe2 )2 }2 ] (2 ) as a stable solid.2 slowly underwent an intramolecular Si–H/H–N dehydrocoupling in solution to give [{(L)SiMe2 N(SiHMe2 )}Sr{N(SiHMe2 )2 }] (3 ) by liberating H2 . The results of transamination of1 with HN(SiHMe2 )2 depended on the relative stoichiometric ratio. A 1 : 1 mixture in n -pentane gave [{(L)SiMe2 N(SiHMe2 )}Sr{N(SiMe3 )2 }] (4 ) and H2, while excess HN(SiHMe2 )2 gave the adduct2 under similar conditions. Compounds2 and3 exhibit Sr↼H–Si interactions according to X-ray crystallography, NMR, and IR spectroscopy. Lighter congeners of elusive [(L)Sr{N(SiHMe2 )2 }] were isolable for Mg (5 ) and Ca (6 ).